Phytochemical Analysis, Antibacterial Activity and Modulating Effect of Essential Oil from Syzygium cumini (L.) Skeels - Priscilla Augusta de Sousa Fernandes; Raimundo Luiz Silva Pereira; Antonia Thassya Lucas dos Santos; Henrique Douglas Melo Coutinho; Maria Flaviana Bezerra Morais-Braga; Viviane Bezerra da Silva; Adrielle Rodrigues Costa; Maria Elizete Machado Generino; Maraiza Gregorio de Oliveira; Saulo Almeida de Menezes; Luciano Temoteo dos Santos; Abolghasem Siyadatpanah; et al. (Molecules, 2022)
One of the main global problems that affect human health is the development of bacterial resistance to different drugs. As a result, the growing number of multidrug-resistant pathogens has contributed to an increase in resistant infections and represents a public health problem. The present work seeks to investigate the chemical composition and antibacterial activity of the essential oil of Syzygium cumini leaves. To identify its chemical composition, gas chromatography coupled to mass spectrometry was used. The antibacterial activity test was performed with the standard strains Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 25853 and Staphylococcus aureus ATCC 25923 and multidrug-resistant clinical isolates E. coli 06, P. aeruginosa 24 and S. aureus 10. The minimum inhibitory concentration (MIC) was determined by serial microdilution as well as the verification of the modulating effect of the antibiotic effect. In this test, the oil was used in a subinhibitory concentration. The test reading was performed after 24 h of incubation at 37 °C. The results show that the major chemical constituent is α-pinene (53.21%). The oil showed moderate activity against E. coli ATCC 25922, with the MIC of 512 µg/mL; there was no activity against the other strains. The oil potentiated the effect of antibiotics demonstrating possible synergism when associated with gentamicin, erythromycin and norfloxacin against E. coli 06 and S. aureus 10.